2007
DOI: 10.1103/physrevlett.98.050405
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation in a Completely Integrable Many-Body Quantum System: AnAb InitioStudy of the Dynamics of the Highly Excited States of 1D Lattice Hard-Core Bosons

Abstract: In this Letter we pose the question of whether a many-body quantum system with a full set of conserved quantities can relax to an equilibrium state, and, if it can, what the properties of such state are. We confirm the relaxation hypothesis through a thorough ab initio numerical investigation of the dynamics of hard-core bosons on a one-dimensional lattice. Further, a natural extension of the Gibbs ensemble to integrable systems results in a theory that is able to predict the mean values of physical observable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
2,038
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,476 publications
(2,081 citation statements)
references
References 50 publications
38
2,038
1
4
Order By: Relevance
“…(3), it is necessary to introduce a number of Lagrange multipliers (see further below), one for each "conserved quantity", which eventually turn into a set of "effective temperatures" {T k eff } determined by the condition ψ 0 |n k |ψ 0 = n k T =T k eff . These quantities prove to be particularly useful since they naturally appear in the calculation of (stationary and non-stationary) expectation values [17,18,20]. It was in fact suggested [17] that the stationary behavior of the system after quenches towards Hamiltonians of the form (7) can be described in terms of the density matrixρ GGE obtained by maximizing the von Neumann entropy S[ρ] under the constraints on the expectation values of n k .…”
Section: A Energy and Constants Of Motionmentioning
confidence: 99%
See 4 more Smart Citations
“…(3), it is necessary to introduce a number of Lagrange multipliers (see further below), one for each "conserved quantity", which eventually turn into a set of "effective temperatures" {T k eff } determined by the condition ψ 0 |n k |ψ 0 = n k T =T k eff . These quantities prove to be particularly useful since they naturally appear in the calculation of (stationary and non-stationary) expectation values [17,18,20]. It was in fact suggested [17] that the stationary behavior of the system after quenches towards Hamiltonians of the form (7) can be described in terms of the density matrixρ GGE obtained by maximizing the von Neumann entropy S[ρ] under the constraints on the expectation values of n k .…”
Section: A Energy and Constants Of Motionmentioning
confidence: 99%
“…In several studies presented in the literature it was shown that a number of quantum isolated systems with short-range interactions reach a stationary state [17,18,20,21,30], while some fully-connected models [33,35,54] and some mean-field approximations to models with short-range interactions [55][56][57] keep a nonstationary behavior. For the isolated quantum Ising chain a stationary state is indeed reached after the quench and we will therefore focus on this relatively simple case.…”
Section: B Dynamic Correlations and Response Functionsmentioning
confidence: 99%
See 3 more Smart Citations